Pipe ramming projects - Najafi, Mohammad (American Society of Civil Engineers, 2008)
Prepared by the Pipe Ramming Task Force of the Trenchless Installation of Pipelines Committee of the Pipeline Division of ASCE. Pipe Ramming Projects presents the latest and best practices used by engineers and construction professionals for the design and construction of road and railroad crossings using pipe ramming technologies. The manual is divided into seven sections and is based upon the results of case studies, workshops, project reviews, technical papers, and other information contributed by industry experts. Part 1 presents general concepts and includes an introduction, history, recent innovations, applicable documents, typical applications, and a glossary of terms. Parts 2 through 5 provide important information on the planning, design, preconstruction, materials, and construction phases of the pipe ramming method. Part 6 presents several case studies, and Part 7 contains a list of references. Providing both introductory and advanced design and construction information to support the safe, cost-effective, and efficient application of the pipe ramming method, this manual will be valuable to both new and experienced engineers, as well as utility owners, contractors, and other industry professionals.
Keywords: Pipelines -- Design and construction.; Trenchless construction.; elektronické knihy; electronic books